2015
DOI: 10.1007/s11999-015-4448-x
|View full text |Cite
|
Sign up to set email alerts
|

What Are Risk Factors for Intraoperative Humerus Fractures During Revision Reverse Shoulder Arthroplasty and Do They Influence Outcomes?

Abstract: Background With the increase in shoulder arthroplasty rates, the number of perioperative complications, such as periprosthetic fractures, continues to be a rise; however, the risk factors and incidence of intraoperative complications, such as fractures, during revision reverse shoulder arthroplasty are not well established. Questions/purposes We evaluated patients receiving a reverse shoulder arthroplasty to determine (1) the frequency and characteristics of intraoperative humerus fractures, (2) the risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 27 publications
0
51
2
2
Order By: Relevance
“…Potential advantages with platform shoulder systems include reduced operative time, blood loss, cost, and length of hospitalization 11, 49,58,[203][204][205][206][207] . The most salient advantage involves reduction in the rate of periprosthetic humeral fracture during revision surgery (Figs.…”
Section: Evolving Trends In Shoulder Arthroplastymentioning
confidence: 99%
“…Potential advantages with platform shoulder systems include reduced operative time, blood loss, cost, and length of hospitalization 11, 49,58,[203][204][205][206][207] . The most salient advantage involves reduction in the rate of periprosthetic humeral fracture during revision surgery (Figs.…”
Section: Evolving Trends In Shoulder Arthroplastymentioning
confidence: 99%
“…24 Although most early RSA were initially designed for cemented fixation of the humeral component, cementless fixation has become very common. Excessive uncontrolled reaming for cementless fixation should be avoided, as it may produce a stress riser area at the end of the reaming area, and may increase the risk of periprosthetic fracture.…”
Section: Intra-operative Fracturesmentioning
confidence: 99%
“…Prior studies have focused on identifying risk factors for complications such as intraoperative humeral fracture, early dislocation, increased transfusion, infection, and nerve injury. 15 Specifically, Wagner et al 8 analyzed 230 RTSA cases and found risk of intraoperative periprosthetic fractures was increased by female gender (OR: 2.41, p ¼ 0.03), history of instability (OR: 2.65, p ¼ 0.02), and prior hemiarthroplasty (OR: 2.34, p ¼ 0.03). Two studies of 73 and 32 RTSA for glenoid loosening found that patients with a full-thickness rotator cuff tear at time of revision surgery had a higher risk of re-operation (p ¼ 0.03), and identified instability, rotator cuff tears, and malunion of the greater tuberosity as risk factors for poor outcomes.…”
Section: Risk Factors For Adverse Events and Unplanned Readmissionmentioning
confidence: 99%
“…He reported that component revision provides the best results while soft-tissue reconstruction provides worse results overall. Another study of 230 revisions of reverse TSA by Wagner et al 8 found that female gender, history of instability, and prior hemiarthroplasty increased risk for post-revision complications. Saltzman et al 9 compared complication rates for 111 primary and 26 RTSAs and found body mass index (BMI) to predict medical complications after primary and RTSA.…”
Section: Introductionmentioning
confidence: 99%